JAVA LANGUAGE IN THE MADURESE CROSS CULTURE - Kholik Kholik; Muhammad Ridwan; Saptono Hadi (Jurusan Sastra Indonesia, 2019)
Indonesian society in general is bilingual. They mastered the first language (B1) of the local language and discussed the second (B2) Indonesian language. There is a small part of the multilingual community, besides mastering BD and BI, also mastering foreign languages. Nevertheless, the mastery process of each language varies according to the development of Indonesian society. Regarding language and culture, the famous adage that has become truism is